Primary actinomycosis of the right upper extremity - an unusual presentation - Dr. Pratibha. S.; Dr. Arundhathi. S.; Dr. Lakshmi. K. S.; Praveen Kumar R. (Tropical Journal of Pathology and Microbiology, 2018)
Actinomycosis is a chronic disease characterized by multiple abscesses, granulomas, tissue destruction, extensive fibrosis and formation of sinuses. We report a case of 45 year old female with primary cutaneous actinomycosis of right upper extremity, which is a very rare site of occurrence. The patient was treated successfully with extended period antimicrobial treatment with Doxycycline (spacing) and Cefixime.